Umbilical artery tone in maternal obesity - Glavey Siobhan V; Moynihan Audrey T; Hehir Mark P; Morrison John J (BMC, 2009)
Abstract Background The increasing prevalence of obesity constitutes a major health problem in obstetrics with implications for feto-maternal growth and wellbeing. This study investigated and compared the contractile properties of umbilical arteries excised from obese women, with those excised from women with a normal body mass index (BMI). Methods Sections of umbilical artery were obtained from umbilical cord samples immediately after delivery and mounted for isometric recording in organ tissue baths under physiological conditions. Cumulative additions of 5-Hydroxytryptamine (5-HT) and Prostaglandin F-2alpha (PgF2alpha) were added in the concentration range of 1 nmol/L to 10 micromol/L. Control vessels were exposed to Krebs physiological salt solution (PSS) only. The resultant effects of each drug addition were measured using the Powerlab hardware unit. Results 5-HT exerted a significant effect on human umbilical artery tone at concentrations of 100 nmol/L, 1 micromol/L, and 10 micromol/L in normal (n = 5; P < 0.05) and obese (n = 5; P < 0.05) women. The contractile effect was significantly greater in vessels from obese women {Mean Maximum Tension (MMT) = 4.2532 g} than in those from women of normal BMI (MMT = 2.97 g; P < 0.05). PgF2alpha exerted a significant contractile effect on vessels at 1 micromol/L and 10 micromol/L concentrations when compared with controls (n = 5; P < 0.05). There was a non-significant trend towards an enhanced tone response in vessels from obese women (MMT = 3.02 g; n = 5), in comparison to vessels from women of a normal BMI (MMT = 2.358 g; n = 5; P > 0.05). Conclusion These findings support the hypothesis that endogenous regulation of umbilical artery tone is altered in association with maternal obesity. This may be linked to the cardiovascular effects of secretory products of adipose tissue, with implications for the feto-maternal circulation.